Gestão de portfólio de convênios: proposição de um instrumento para a seleção de projetos na universidade federal da integração latino-americana - Santos, Elaine Michele Diniz (2023)
Considering the budget scarcity in which Federal Institutions of Higher Education find themselves and the difficulties encountered in maintaining their core activities, which are of paramount importance for society, the signing of agreements with public or private organizations appears as an important alternative to meet such needs and avoid scrapping. Agreements are originally projects/work plans that intend to share the management of an object and define how this object will be executed and how the parties will contribute. The problem related to the theme consists in the fact that there are no defined criteria for the selection of projects that will compose the portfolio of agreements and similar instruments at the Federal University of Latin American Integration. In the meantime, this work proposes the construction of a decision support instrument for the selection of strategic projects through the MCDA-C methodology. A Systematic Literature Review was carried out to assess the state of the art of the subject of agreements in the IFES. The result of this research supports the construction of criteria and descriptors of the selection tool proposed in this work. Having this preliminary information, we set out to build the tool. Finally, the proposed instrument is submitted to a validation process with real samples of health insurance. The results obtained with the validation demonstrate that the tool is able to support the decision in a satisfactory way through the ranking and classification of the projects in a quantitative and judicious way. In this way, decision makers are able to evaluate and select projects from different perspectives, point out justifications for their urgency or even suggest improvements to proponents.